Migraine Genetics – A Review: Part I. Issue 8 (12th July 2013) - Silberstein, Stephen; Dodick, David
Abstract : Significant progress in molecular genetics has advanced our understanding of the genetic basis of migraine. The fundamentals of molecular genetics, and the recent advances in the field, are important for clinicians to understand, as they provide a foundation for critical appraisal of the literature, unprecedented insights into the pathogenesis of the disorder, and reveal promising treatment targets for future drug development. This paper provides a primer of molecular genetics and will be followed by a companion paper on the genetic advances in migraine, the methodology of genome wide association studies, and the potential clinical implications.